Thirteen days of "live high-train low" does not affect prooxidant/antioxidant balance in elite swimmers - Pialoux, V.; Mounier, R.; Brugniaux, J. V.; Rock, E.; Mazur, A.; Richalet, J. P.; Robach, P.; Coudert, J.; Fellmann, N. (European Journal of Applied Physiology, 2009)
We investigated the impact of 13 days of "living high-training low" (LHTL) on the antioxidant/prooxidant balance in elite endurance swimmers. Eighteen elite swimmers from the French Swimming Federation were submitted to a 13-day endurance training and divided into two groups: one group trained at 1,200 m and lived in hypoxia (2,500-3,000 m simulated altitude) and the second group trained and lived at 1,200 m. The subjects performed an acute hypoxic test (10 min at 4,800 m) before and 1 day after the training period. Plasma levels of advanced oxidation protein products (AOPP), malondialdehydes (MDA), ferric reducing antioxidant power (FRAP), and lipid-soluble antioxidants were measured before and after the 4,800 m tests. After the training, MDA and AOPP responses to the 4,800 m test were lower than before training for both groups (+10 vs. +2%; P = 0.01 for MDA and +80 vs. +14%; P = 0.01 for AOPP). Thirteen days of LHTL did not modify antioxidant status (FRAP and lipid-soluble antioxidants) despite intakes in vitamins A and E below the recommended daily allowances. The LHTL did not affect the antioxidant status in elite swimmers; however, the normoxic endurance training induced preconditioning mechanisms in response to the 4,800 m test.